Polychlorinated Biphenyls in Residential Dust: Sources of Variability - Whitehead, Todd P. (2013)
We characterized the variability in concentrations of polychlorinated biphenyls (PCBs) measured in residential dust. Vacuum cleaner samples were collected from 289 homes in the California Childhood Leukemia Study during two sampling rounds from 2001 to 2010 and 15 PCBs were measured by high resolution gas chromatography–mass spectrometry. Median concentrations of the most abundant PCBs (i.e., PCBs 28, 52, 101, 105, 118, 138, 153, and 180) ranged from 1.0–5.8 ng per g of dust in the first sampling round and from 0.8–3.4 ng/g in the second sampling round. For each of these eight PCBs, we used a random-effects model to apportion total variation into regional variability (6–11%), intra-regional between-home variability (27–56%), within-home variability over time (18–52%), and within-sample variability (9–16%). In mixed-effects models, differences in PCB concentrations between homes were explained by home age, with older homes having higher PCB levels. Differences in PCB concentrations within homes were explained by decreasing time trends. Estimated half-lives ranged from 5–18 years, indicating that PCBs are removed very slowly from the indoor environment. Our findings suggest that it may be feasible to use residential dust for retrospective assessment of PCB exposures in studies of children’s health.